Error free backbone tree construction to expand the longevity of wireless. (19th July 2019) - Stephen, K. Vimal Kumar; Mathivanan, V.
Wireless sensor networks (WSN) raises number of the challenges with regard to scalability and energy efficacy. Implemented of Huffman approaches one of the key variable length in the wireless sensor network is prolonging network lifetimes. To improve the lifetime of the sensor, static and movable mobile sinks are deployed. Movable sinks are used to receive sensed data from the sensor where it is located. Assigning prime number as the sensor node identity can be easily guessed by the intruder. Reusing the same identity in the cluster leads to compromising of nodes. The energy is retained when computation is reduced in cluster head thereby increases the life time of the particular cluster. Variable length gives variable length identity and avoids reusing of same identity hence it avoid network attacks such as random number length of nodes are not possible (no sensors are allowed inside the network without the knowledge of cluster head). Increasing transmission range future will consume more battery power.